Content Analysis and Student Perceptions of “Ayo Fasih Berbahasa Arab” Book - Misdayanti, Annisah; Roojil Fadillah (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to analyze the suitability of the textbook "Ayo Fasih Berbahasa Arab" for grade XI of Madrasah Aliyah based on The 2024 Assessment Instrument by the Center for Research and Development of Literature, Religious Heritage, and Organizational Management (LKKMO 2024), and to explore students’ perceptions regarding its effectiveness in Arabic language learning. A descriptive, qualitative approach was employed, utilizing content analysis and descriptive statistics. The research involved 41 students from XI Science 1 and 2 classes at SMA Daarut Tauhid Putri, Bandung. The researcher employed a descriptive qualitative research method, with data collected through observation, questionnaires, and documentation. The LKKMO 2024 instrument evaluates four aspects: content/material, presentation, language and religious terminology, and graphics. The results indicate that the textbook scored “very good” in content, presentation, and language use, but only “fairly good” in graphics due to inconsistent illustrations. Student responses indicated that 72.7% found the textbook suitable for their learning level and effective in supporting their reading and speaking skills. However, the development of listening skills remains a challenge. This research contributes to improving Arabic textbooks aligned with curriculum standards and learners’ needs. The findings are expected to guide educators and policymakers in enhancing the quality of teaching materials. While the book is considered effective overall, further refinement is recommended, particularly in the listening component and in creating a more cohesive visual presentation to optimize learning outcomes.